AURKA inhibition induces Ewing’s sarcoma apoptosis and ferroptosis through NPM1/YAP1 axis - Huimou Chen; Jing Hu; Xilin Xiong; Hongling Chen; Biaojun Lin; Yusong Chen; Yang Li; Di Cheng; Zhihua Li (Cell Death and Disease, 2024)
Abstract Ewing’s sarcoma (ES) is a rare and highly aggressive malignant tumor arising from bone and soft tissue. Suffering from intractable or recurrent diseases, the patients’ therapy options are very limited. It is extremely urgent to identify novel potential therapeutic targets for ES and put them into use in clinical settings. In the present study, high-throughput screening of a small molecular pharmacy library was performed. The killing effect of the Aurora kinase A (AURKA) inhibitor TCS7010 in ES cells was identified, and AURKA was selected as the research object for further study. Disparate suppressants were adopted to study the cell death manner of TCS7010. TCS7010 and RNA silencing were used to evaluate the functions of AURKA in the apoptosis and ferroptosis of ES cells. Co-immunoprecipitation assay was used to investigate the correlation of AURKA and nucleophosmin1 (NPM1) in ES. Nude-mice transplanted tumor model was used for investigating the role of AURKA in ES in vivo. Investigations into the protein activities of AURKA were conducted using ES cell lines and xenograft models. AURKA was found to be prominently upregulated in ES. The AURKA expression level was remarkably connected to ES patients’ shorter overall survival (OS) and event-free survival (EFS). Furthermore, AURKA inhibition markedly induced the apoptosis and ferroptosis of ES cells and attenuated tumorigenesis in vivo. On the part of potential mechanisms, it was found that AURKA inhibition triggered the apoptosis and ferroptosis of ES cells through the NPM1/Yes1 associated transcriptional regulator (YAP1) axis, which provides new insights into the tumorigenesis of ES. AURKA may be a prospective target for clinical intervention in ES patients.